PENERAPAN SISTEM PENGELOLAAN SAMPAH PADA ALAT PEMILAH SAMPAH ORGANIK DAN ANORGANIK BERBASIS CONVEYOR DI TPS TANJUNG BARANGAN - Perdana, Aditya; Rahman, A.; Kusumanto, RD. (JURNAL TELISKA, 2023)
The Waste is a prevalent problem in Indonesia, causing environmental pollution, diseases such as dengue, malaria, vomiting, and diarrhea, as well as emitting strong odors in residential areas. Waste sorting is an effective solution to address this issue. Implementing the Conveyor-Based Organic and Inorganic Waste Sorting Tool technology at Tanjung Barangan can help to overcome waste problems in residential areas and facilitate the decomposition and recycling process. This research aims to assess the reliability of capacitive, inductive, and infrared proximity sensors in waste sorting. The study found that the system performed well. The capacitive proximity sensor successfully detected organic waste with a success rate of 75%, while the inductive proximity sensor detected inorganic waste with a success rate of 70%. Once the waste is detected, the information is displayed on the LCD screen, and it is sorted directly into the appropriate trash box based on its type, whether organic or inorganic.The proximity sensors have different detection distances: capacitive proximity sensors can detect objects within a range of 0 to 6 mm, inductive proximity sensors have a range of 0 to 10 mm, and infrared proximity sensors can detect objects within a range of 0 to 14 mm.